Poisoning From Specific Toxic Agents to Novel Rapid and Simplified Techniques for Analysis - Malangu, Ntambwe (IntechOpen, 2017)
This book, which is the result of contributions from a team of international authors, presents a collection of materials that can be categorized into two groups. The first group of papers deals with clinical toxicology topics including poisoning by anticoagulant rodenticides, food toxins, carbon monoxide, the toxicity of beta-lactam antibiotics, acute neonicotinoid poisoning, occupational risk factors for acute pesticide poisoning, activating carbon fibers, and date pits for use in liver toxin adsorption. The second group of papers deals with forensic or analytical toxicology topics such as simplified methods for the analysis of gaseous toxic agents, rapid methods for the analysis and monitoring of pathogens in drinking water and water-based solutions, as well as the linkages between clinical and forensic toxicology. Each chapter presents new information on the topic discussed based on authors' experience while summarizing existing knowledge. As such, this book will be a good teaching aid and can be a prescribed or recommended reading for postgraduate students and professionals in the fields of public health, medicine, pharmacy, nursing, biology, toxicology, and forensic sciences.